Legacy effects of four decades of insecticide applications on contemporary riverine benthic macroinvertebrates - Scott Sugden; Amy B. White; Jennifer Lento; Joshua Kurek; Ilya Dimitrovas; Sandra Emry; Xiaotian Hua; Moira M. Ijzerman; Karen A. Kidd; Katlyn LM. Morrow; Jessica E. Ollinik; Laura Schnell; et al. (Environmental Pollution, 2025)

Historical pesticide applications for the treatment of eastern spruce budworm infestations in New Brunswick - Shane Heartz; David A. MacLean; Rob C. Johns; Drew Carleton; Luke Amos‐Binks; Quinn Anderson; Yue Yu; Andrew D. Lewis; Dan Lavigne; Joseph B. Burant; Christopher B. Edge (Ecology, 2023)
Pesticides have been used in Canada since 1945 as part of large‐scale aerial spray applications to control insect pests on forested lands. Some of the pesticides used historically were efficacious, nonselective, persistent, and have led to serious impacts on the environment. A well known, and extensively documented example is the large‐scale aerial spray programs in New Brunswick, Canada. From 1952 to 1993, 97% of the 6.2 million ha of the forested lands of New Brunswick were treated with at least one application of one insecticide, the majority of which were applied to control outbreaks of eastern spruce budworm ( Choristoneura fumiferana ). The most well known insecticide was dichlorodiphenyltrichloroethane (DDT), applied from 1952 to 1968, which still persists in treated soils and adjacent water bodies, and caused the individual and cumulative ecosystem effects that can still be measured today. The insecticides that replaced DDT were nonpersistent and unlikely to be found today. However, during the years of application some of the insecticides were likely to have impacted local ecosystems to some degree. To aid future studies on the efficacy and environmental impact of these insecticides we created a digital spatial data set of known pesticide application in New Brunswick forestry from 1952 to 1993. The data set includes active ingredient, formulation, application rate, tank mix, aircraft type, and other ancillary information. The current version of the data is available on the New Brunswick Department of Natural Resources and Energy Development, GIS Open Data Page and in the supplemental material. Use of the data set for academic and educational purposes is encouraged, provided that both this data paper and the data source are properly cited; the Government of New Brunswick should be acknowledged as the data source (Open Government License http://www.snb.ca/e/2000/data-E.html ).

Phenotypic plasticity of nest timing in a post‐glacial landscape: how do reptiles adapt to seasonal time constraints? - Christopher B. Edge; Njal Rollinson; Ronald J. Brooks; Justin D. Congdon; John B. Iverson; Fredric J. Janzen; Jacqueline D. Litzgus (Ecology, 2017)
Life histories evolve in response to constraints on the time available for growth and development. Nesting date and its plasticity in response to spring temperature may therefore be important components of fitness in oviparous ectotherms near their northern range limit, as reproducing early provides more time for embryos to complete development before winter. We used data collected over several decades to compare air temperature and nest date plasticity in populations of painted turtles and snapping turtles from a relatively warm environment (southeastern Michigan) near the southern extent of the last glacial maximum to a relatively cool environment (central Ontario) near the northern extent of post‐glacial recolonization. For painted turtles, population‐level differences in reaction norm elevation for two phenological traits were consistent with adaptation to time constraints, but no differences in reaction norm slopes were observed. For snapping turtle populations, the difference in reaction norm elevation for a single phenological trait was in the opposite direction of what was expected under adaptation to time constraints, and no difference in reaction norm slope was observed. Finally, among‐individual variation in individual plasticity for nesting date was detected only in the northern population of snapping turtles, suggesting that reaction norms are less canalized in this northern population. Overall, we observed evidence of phenological adaptation, and possibly maladaptation, to time constraints in long‐lived reptiles. Where present, (mal)adaptation occurred by virtue of differences in reaction norm elevation, not reaction norm slope. Glacial history, generation time, and genetic constraint may all play an important role in the evolution of phenological timing and its plasticity in long‐lived reptiles.

Microbes in beach sands: integrating environment, ecology and public health - Richard L. Whitman; Valerie J. Harwood; Thomas A. Edge; Meredith B. Nevers; Muruleedhara Byappanahalli; Kannappan Vijayavel; João Brandão; Michael J. Sadowsky; Elizabeth Wheeler Alm; Allan Crowe; Donna Ferguson; Zhongfu Ge; et al. (Reviews in Environmental Science and Bio/Technology, 2014)

Recurrent violations of invariant rules for offspring size: evidence from turtles and the implications for small clutch size models - Njal Rollinson; Christopher B. Edge; Ronald J. Brooks (Oecologia, 2013)

Differences in the Phenotypic Mean and Variance Between Two Geographically Separated Populations of Wood Frog (Lithobates sylvaticus) - Christopher B. Edge; Dean G. Thompson; Jeff E. Houlahan (Evolutionary Biology, 2013)